Outer Divertor Damage Characterization from Deuterium Plasma Bombardment in Graphene-Coated Tungsten in the C-2W Device. (18th August 2019) - Navarro, Marcos X.; Zamiri, Marziyeh; Griswold, Martin E.; Santarius, John F.; Kulcinski, Gerald L.; Lagally, Max; Tajima, Toshiki
Abstract: This research explores the performance of graphene as a coating for plasma-facing components (PFCs) in a nuclear fusion environment. Our recent studies have shown that graphene can act as a resistant layer against plasma exposure and ion bombardment. PFCs tend to develop surface morphologies that lead to mass loss of the wall material, potentially diminishing their lifetime and degrading plasma performance. We present a characterization of graphene-coated samples of W irradiated in the C-2W divertor. Energy analyzers were used to determine average ion fluxes to the samples on the order of 10 18 D + /cm 2 . Two samples were exposed over 1210 plasma discharges. Raman spectroscopy showed that slow ions (30 < E < 100 eV) interact strongly with the graphene, introducing vacancies into the membrane (ID /IG  ~ 0.7), making it possible to assess the limiting factors on such a coating's lifetime. We also found that graphene slows down impurity deposition on the material surfaces due to graphene's stable configuration and low surface energy. This first attempt at testing the coating in a large-scale fusion experiment aims to expand the possible wall candidates for PFCs.